Temporal and spatial variation of radiocaesium in moose (Alces alces) following the Chernobyl fallout in Sweden - Weimer, Robert N. (2015)
In my thesis, I have analysed long-term monitoring data of ¹³⁷Cs activity concentrations in moose (Alces alces) from the two Swedish municipalities Heby and Gävle. These study areas are adjacent and dominated by managed coniferous forests. The percentage of farmland in Heby is 20% but only 4% in the Gävle area. Heby is located about 70 km inland from the Baltic coast while the study site Gävle is more close to the border of to the Baltic Sea. The decline in the annual geometric mean ¹³⁷Cs concentrations in moose from 1986 to 2012 for Heby and 1986-2008 for Gävle corresponds to an effective ecological half-life of 16 years for both areas. Calves were found to have higher ¹³⁷Cs-concentrations than adults, on the average 14% (SD=18%) and 18% (SD=7%) in the Heby and Gävle areas, respectively. The aggregated transfer of ¹³⁷Cs, that describes the transfer rate from soil (activity per m²) to moose muscle (activity per kg), seemed to be higher in Gävle (0.023 kg m⁻²) than in Heby (0.016 kg m⁻²). The separate data sets were modelled by partial least squares regression (PLS) to examine the influence of environmental and physiological parameters on the caesium uptake by moose. Both data sets were supplemented with information on weather conditions prior to the hunting season, i.e. June-September. The Heby data set was more comprehensive and contained coordinates of most killing sites. That made it possible to add information of habitat types and estimated mean ground deposition around each killing site. The results of the PLS-analysis revealed at to which degree the examined parameters influenced the uptake of ¹³⁷Cs by moose. Apart from time since the accident and the amount of deposition, the most dominating parameters were the proportion of different habitat types around the killing site and the moose age. The model based on the more detailed Heby data set, explained the variation in ¹³⁷Cs concentrations in moose to a higher degree, than the model based on the Gävle data set. These results contribute to better ...